Comparison of Viscum album QuFrF Extract with Vincristine in an in vitro Model of Human B Cell Lymphoma WSU-1 - Kovacs, Eva; Link, Susanne; Toffol-Schmidt, Ulrike (Arzneimittelforschung, 2008)
L. extract (Iscador®) with different preparations is used either alone or in combination with chemo/radiotherapy in the treatment of patients with various tumours. Vincristine (CAS 57-22-7) as a chemotherapeutic agent is used mainly in combination with other chemotherapeutic substances in the therapy of B cell lymphoma. In this study, the effects of Viscum album (VA) QuFrF extract and vincristine were compared on B cell lymphoma cell line WSU-1 in an in vitro model. As parameters were measured: proliferation, viability, apoptosis/necrosis, IL-6 production, DNA synthesis and the cell cycle phases of the lymphoma cells at various time points.The cytostatic (inhibition of proliferation) effects of VAQuFrF and vincristine at 10 ug/105 cells were the same at 48 h and 72 h. This means that the antiproliferative effect of 2 ng lectin (in 10 µg extract) is equivalent to 10 µg of vincristine. There was a relationship between the cytostatic and cytocidal (killing of viable cells) effects for both substances. This means that both substances first inhibit the proliferation of the tumour cells, and then the cells die by apoptosis or necrosis. VAQuFrF and vincristine reduced the DNA synthesis markedly and arrested the G2/M cell cycle phase. Both substances led to a clearly dose-dependent apoptosis at 12 h and 24 h. Neither VAQuFrF nor vincristine led to IL-6 production of the lymphoma cells.The effects of VAQuFrF on the B cell lymphoma cell line WSU-1 were comparable to those of vincristine in all parameters. The effective dose range lay between 50 and 100 µg/106 cells for VAQuFrF, for vincristine it was somewhat lower.
Keywords: B cell lymphoma cells, apoptosis, necrosis, WSU-1 cell line; CAS 57-22-7; Chemotherapeutics; Iscador®; Vincristine; Viscum album L. QuFrF extract, human B cell lymphoma, in vitro studies